2013
DOI: 10.1186/1471-2091-14-16
|View full text |Cite
|
Sign up to set email alerts
|

Experimental detection of proteolytic activity in a signal peptide peptidase of Arabidopsis thaliana

Abstract: BackgroundSignal peptide peptidase (SPP) is a multi-transmembrane aspartic protease involved in intramembrane-regulated proteolysis (RIP). RIP proteases mediate various key life events by releasing bioactive peptides from the plane of the membrane region. We have previously isolated Arabidopsis SPP (AtSPP) and found that this protein is expressed in the ER. An AtSPP-knockout plant was found to be lethal because of abnormal pollen formation; however, there is negligible information describing the physiological … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
7
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 30 publications
1
7
0
Order By: Relevance
“…Many studies also indicate that intramembrane protease performs crucial functions in providing plant fertility. Aberrations in flower, pollen or silique development were observed in rbl10 and atkom mutants as well as in spp (Thompson et al 2012, Hoshi et al 2013. The transcripts of SPPL1, SPPL2 and SPPL3 proteins accumulate in turn during seed germination, but their role in this process remains unexplored.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…Many studies also indicate that intramembrane protease performs crucial functions in providing plant fertility. Aberrations in flower, pollen or silique development were observed in rbl10 and atkom mutants as well as in spp (Thompson et al 2012, Hoshi et al 2013. The transcripts of SPPL1, SPPL2 and SPPL3 proteins accumulate in turn during seed germination, but their role in this process remains unexplored.…”
Section: Resultsmentioning
confidence: 99%
“…Continuously accumulating data indicate; however, that their role in development should not be underestimated. A mutation in the SPP gene was demonstrated to be lethal (Hoshi et al 2013). Many studies also indicate that intramembrane protease performs crucial functions in providing plant fertility.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Four families of multispanning membrane proteases, S2P, rhomboid, presenilin, and signal peptide peptidase (SPP), have been well characterized in animals. Substrates of two other multispanning membrane proteases, presenilin, and SPP (Smolarkiewicz et al, 2014;Han et al, 2009;Hoshi et al, 2013;Tamura et al, 2009), remain to be identified in plants. Rhomboid is encoded by multiple genes in the Arabidopsis genome (Kanaoka et al, 2005) and is proposed to be required for proteolytic cleavage of ANAc017 as described in Section 25.3.5.…”
Section: Conclusion and Future Perspectivesmentioning
confidence: 99%